The Role of Anatomical Imaging and Intraoperative Neuromonitoring (IONM) for Successful Prediction of a Nonrecurrent Laryngeal Nerve - Hiroki Kuwazoe; Keisuke Enomoto; Daichi Murakami; Naoko Kumashiro; Saori Takeda; Muneki Hotomi (Case Reports in Surgery)
A nonrecurrent laryngeal nerve (NRLN) is a rare anatomical variant of laryngeal nerves that branches directly from the vagus nerve. The anatomical abnormality makes it difficult to identify the NRLN and results in high incidence of accidental nerve injury during surgery. A 76-year-old woman complained of swelling in the right side of her neck and visited our university hospital for further examination. Ultrasonography showed a right thyroid lobe mass with calcification and fine needle aspiration biopsy was classified as class III. Computed tomography revealed that the right subclavian artery branched directly from the descending aorta without branching from the brachiocephalic artery and ran behind the esophagus. Since it was afraid that the accidental injury of NRLN was likely to occur, a right thyroid lobe dissection using intraoperative neuromonitoring (IONM) was performed. After separating the connective tissue on the thyroid capsule from the right side of the trachea to the inferior pole laterally, the NRLN running across the level of the inferior margin of the cricoid cartilage was identified by using IONM 0.5 mA stimulation. After complete dissection of right thyroid lobe, we again stimulated the NRLN by 0.5 mA and the electromyographic response was confirmed. The pathological analysis confirmed nodular hyperplasia without malignancy; the condition was diagnosed as an adenomatous goiter. There was no vocal cord dysfunction and hoarseness after the surgery. IONM contributed to the prevention of NRLN injury during the surgery. We believe that it is important to confirm the presence or absence of an aberrant subclavian artery on preoperative imaging, and that IONM should be considered to identify the NRLN to prevent vocal cord paralysis if its presence is suspected.